2022
DOI: 10.1002/nop2.1207
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of the COVID‐19 pandemic on nursing students in the first wave: A cross‐sectional survey

Abstract: Aim The aim of the study was to evaluate the psychological impact on nursing students at the end of period of confinement during the first wave of the COVID‐19 outbreak in Spain. Design A cross‐sectional study reported in line with the STROBE guidelines. Methods Nursing students were invited to complete an online questionnaire at the end of the 2019–2020 academic year using convenience sampling. The questionnaire collected data on sociodemographic factors, work, and life experiences in relation to COVID‐19, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
2
6
1
2
Order By: Relevance
“…Our results also indicated adequate negative correlations between well-being and anxiety, consistent with a previous study that found strong correlations between the WHO-5 Well-Being Index and anxiety [ 29 ]. Additionally, adequate negative correlations were found between well-being and depression, consistent with previous studies reporting that the WHO-5 correlated negatively with depression [ 28 , 47 , 48 , 49 , 50 , 51 , 52 ]. Together with the obtained internal consistency values, these findings support the construct validity of the well-being scale.…”
Section: Discussionsupporting
confidence: 89%
“…Our results also indicated adequate negative correlations between well-being and anxiety, consistent with a previous study that found strong correlations between the WHO-5 Well-Being Index and anxiety [ 29 ]. Additionally, adequate negative correlations were found between well-being and depression, consistent with previous studies reporting that the WHO-5 correlated negatively with depression [ 28 , 47 , 48 , 49 , 50 , 51 , 52 ]. Together with the obtained internal consistency values, these findings support the construct validity of the well-being scale.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, compared with the study by Roldán-Merino et al, 61 which examined a sample of nursing students using the WHO-5 in 2020, our findings revealed higher levels of well-being. The disparities may be attributed to the timing of the surveys as well as the critical exposure of frontline health care professionals during the first months of COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 55%
“…Volume 2 No. 1, June 2022 penyakit degeneratif seperti diabetes mellitus, hipertensi, jantung dan penyakit lainnya menjadi kontra indikasi untuk dilakukan vaksin anti COVID-19 (Carey et al, 2022;Milne & Xie, 2020;Roldán-Merino et al, 2022). Sehingga perlu ada upaya yang dapat menurunkan dampak dari masyarakat yang mengalami dampak virus COVID-19.…”
Section: Community Services and Social Work Bulletinunclassified